Genomic and proteomic repository of chitin degrading bacterium Serratia proteamaculans 568 - Parvati Sai Arun, PV (International Journal of Computer Sciences and Engineering, 2025)
In this paper, we describe about a repository which is composed of the information related to genes sequences, proteins sequences, upstream sequences, codon usage in proteins, physico-chemical properties, secondary structures and biochemical pathway information of proteins of chitin degrading bacterium Serratia proteomaculans 568. The advantage of this repository is that it can be hosted in the user’s computer and work without internet connection. The backend data for developing this repository was generated using different computational tools which were published earlier. The .faa, .fna, .ptt files of S.proteomaculans 568 were downloaded from NCBI was used as primary seed data for the generation backend data. Web technologies were used to retrieve and display the compiled data in the browser. The data retrieved out of this repository can be used as preliminary source for understanding various concepts related to genes and proteins of Serratia proteomaculans 568. This repository can be obtained from http://crraoaimscs.res.in/serratia_568/serratia_568.rar